1994
DOI: 10.3109/01902149409064384
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Clearance of Silica from Mouse Lung After Instillation of a Leukocyte Chemotactic Factor

Abstract: It has been suggested that increased recruitment of phagocytes and subsequent clearance of particles may follow instillation of a leukocyte chemoattractant to lungs containing silica. The present study quantitated serially the silica content in alveolar spaces, in lung tissue and in hilar lymph nodes of mice that received 2 mg silica only, compared to a group that also received 100 micrograms intratracheal chemotactic factor N-formyl-L-methionyl-leucyl-phenylalanine (FMLP) at 2 and 3 weeks after silica. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
(3 reference statements)
3
2
0
Order By: Relevance
“…Although the particle size ͑30 nm diam͒ is too large for excretion through the kidneys and urinary system, 32 the localization of the particles within the mononuclear phagocyte system indicates that the particles may be scavenged and cleared by macrophages consistently with results from pulmonary silica particle exposure. [33][34][35] This possibility is in agreement with our observation that the average dot fluorescence per cell remained relatively constant ͓Fig. 6͑b͔͒.…”
Section: Resultssupporting
confidence: 88%
“…Although the particle size ͑30 nm diam͒ is too large for excretion through the kidneys and urinary system, 32 the localization of the particles within the mononuclear phagocyte system indicates that the particles may be scavenged and cleared by macrophages consistently with results from pulmonary silica particle exposure. [33][34][35] This possibility is in agreement with our observation that the average dot fluorescence per cell remained relatively constant ͓Fig. 6͑b͔͒.…”
Section: Resultssupporting
confidence: 88%
“…We have previously shown that community-sampled geogenic PM 10 induces a potent inflammatory response in the lung [9] . This neutrophil dominated response is consistent with many previous studies examining the lung response to inhaled dusts (primarily SiO 2 ) of mineral origin [18] , [26] . While exposure to crystalline silica in mouse models elicits fibrotic changes [27] , [28] , which presumably alters lung function, there appears to be very little data in the literature on the impact of silica on lung function in mouse models (although silicosis in humans is associated with impaired lung function [29] ).…”
Section: Discussionsupporting
confidence: 91%
“…The 100 µg dose was chosen based on the dose-response data from our previous study [9] as a dose that produces a robust and measurable inflammatory response. This dose (∼5 mg.kg −1 ) is an order of magnitude smaller than typical rodent particle exposure models (∼100 mg.kg −1 [18] ) and is consistent with our prior work on diesel exhaust particles [19] , [20] .…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…The balance between clearance and retention of crystalline silica in the lungs by AM plays an important role in regulating the inflammatory response and silicosis. Previous studies indicate that facilitating the clearance of crystalline silica from the alveolar and interstitial compartments decreases the fibrotic response in the lung (Adamson et al, 1992(Adamson et al, , 1994. Therefore, unsuccessful clearance of crystalline silica may result in persistent inflammation due to prolonged interaction of particles with both immune and non-immune cell populations such as neutrophils, AM, dendritic cells (DCs), and epithelial cells in the lung.…”
mentioning
confidence: 99%